Accurate Estimation of Commercial Volume in Tropical Forests. Issue 1 (6th October 2020) - de Lima, Robson Borges; Rutishauser, Ervan; da Silva, José Antônio Aleixo; Guedes, Marcelino Carneiro; Herault, Bruno; de Oliveira, Cinthia Pereira; da Silva Aparício, Perseu; Sotta, Eleneide Doff; da Silva, Diego Armando Silva; Ferreira, Rinaldo Luiz Caraciolo
Abstract: Accurate estimates of commercial volume in tropical forests are key for the implementation of sustainable forest management plans. Because of the lack of local or generic volumetric equations, most forest managers and forestry services are still using traditional expansion factors (i.e., multiplication of the diameter by a given value) to estimate the volume of commercial tree species in the Amazon. Volumetric models were developed through a unique data set of 1, 264 fallen trees fully measured in 150 sample plots located across a broad range of forests in Amapá, Brazil. Forest-specific volumetric models were developed and compared with a generic (i.e., across all forests) model and with published equations developed elsewhere in the Amazon. The generic equation performed well in all forest types and allowed precise predictions. The most efficient sampling design to develop volumetric models consists of measuring approximately 50 trees across four different size classes representing the whole population. The form factors (FF) developed locally generated substantial bias but performed better than the traditional FF (0.7). Overall, our results suggest that it is possible to develop accurate generic models to estimate commercial timber volume, and this study can serve as a guideline for forest managers or scientists interested in calibrating volumetric models in a cost-efficient way.